The role of neutrophils in the development of liver diseases - Xu, Ruonan (Nature Publishing Group, 2014)
Liver disease encompasses a wide variety of liver conditions, including liver failure, liver cirrhosis and a spectrum of acute and chronic hepatitis, such as alcoholic, fatty, drug, viral and chronic hepatitis. Liver injury is a primary causative factor in liver disease; generally, these factors include direct liver damage and immune-mediated liver injury. Neutrophils (also known as neutrophilic granulocytes or polymorphonuclear leukocytes (PMNs)) are the most abundant circulating white blood cell type in humans, and PMNs are a major innate immune cell subset. Inappropriate activation and homing of neutrophils to the microvasculature contributes to the pathological manifestations of many types of liver disease. This review summarizes novel concepts of neutrophil-mediated liver injury that are based on current clinical and animal model studies.